Synergistic bioconversion of organic waste by black soldier fly (Hermetia illucens) larvae and thermophilic cellulose-degrading bacteria - Shao, Mingying; Zhao, Xiao; Rehman, Kashif Ur; Cai, Minmin; Zheng, Longyu; Huang, Feng; Zhang, Jibin (Frontiers in Microbiology, 2024)
Introduction This study examines the optimum conversion of Wuzhishan pig manure by Black Soldier Fly Larvae (BSFL) at various phases of development, as well as the impact of gut microbiota on conversion efficiency. Method and results In terms of conversion efficiency, BSFL outperformed the growing pig stage (GP) group, with significantly higher survival rates (96.75%), fresh weight (0.23 g), and larval conversion rate (19.96%) compared to the other groups. Notably, the GP group showed significant dry matter reductions (43.27%) and improved feed conversion rates (2.17). Nutritional composition varied, with the GP group having a lower organic carbon content. High throughput 16S rRNA sequencing revealed unique profiles, with the GP group exhibiting an excess of Lactobacillus and Clostridium. Promising cellulose-degrading bacteria in pig manure and BSFL intestines, including Bacillus cereus and Bacillus subtilis, showed superior cellulose degradation capabilities. The synergy of these thermophilic bacteria with BSFL greatly increased conversion efficiency. The BSFL1-10 group demonstrated high growth and conversion efficiency under specific conditions, with remarkable larval moisture content (71.11%), residual moisture content (63.20%), and waste reduction rate (42.28%). Discussion This study sheds light on the optimal stages for BSFL conversion of pig manure, gut microbiota dynamics, promising thermophilic cellulose-degrading bacteria, and the significant enhancement of efficiency through synergistic interactions. These findings hold great potential for sustainable waste management and efficient biomass conversion, contributing to environmental preservation and resource recovery.